1997
DOI: 10.4141/s96-103
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of nitrous oxide emissions from agricultural fields over 28 months

Abstract: Field studies conducted throughout the calendar year are needed to improve flux estimates for the greenhouse gas nitrous oxide (N2O). In this study, we report monthly N2O emissions measured using micrometeorological techniques and a Tunable Diode Laser Trace Gas Analyzer (TDLTGA). Nitrous oxide fluxes were measured at the Elora Research Station (20 km north of Guelph, Ontario) from July to November 1992, and from March 1993 to February 1995, giving a total of 2445 daily averages obtained during the full length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(88 citation statements)
references
References 28 publications
4
82
0
2
Order By: Relevance
“…For example, Wagner-Riddle et al (1997) observed cumulative spring emissions of between 1.46 and 4.34 kg N 2 O-N ha -1 from their fallow and cropped plots. Even if the fluxes observed at Laird are extrapolated over a longer time period they do not come close to the emissions observed in the Wagner-Riddle et al (1997) study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Wagner-Riddle et al (1997) observed cumulative spring emissions of between 1.46 and 4.34 kg N 2 O-N ha -1 from their fallow and cropped plots. Even if the fluxes observed at Laird are extrapolated over a longer time period they do not come close to the emissions observed in the Wagner-Riddle et al (1997) study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wagner-Riddle et al (1997) observed cumulative spring emissions of between 1.46 and 4.34 kg N 2 O-N ha -1 from their fallow and cropped plots. Even if the fluxes observed at Laird are extrapolated over a longer time period they do not come close to the emissions observed in the Wagner-Riddle et al (1997) study. Van Bochove et al (2000) detected order-of-magnitude differences between years (i.e., 0.4 to 10 kg N 2 O-N ha -1 ), which they attributed primarily to differences in the soil moisture conditions in the preceding year and to the timing, depth, and physical attributes of the snowpack.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus plant residues of leguminous species with high nitrogen concentrations would increase nitrogen availability in soils, resulting in increased N 2 O emission rates. For example, N 2 O flux at a site where wheat was cultivated with a leguminous crop was greater than that at a wheat monoculture site [Nishimura et al, 2005;Wagner-Riddle et al, 1997]. Because large amounts of nitrogen are continuously supplied to soils through plant litterfall, leguminous plantations raise nitrogen availability in the soil, making these plantations a possible N 2 O source [Intergovernmental Panel on Climate Change (IPCC), 2003].…”
Section: Introductionmentioning
confidence: 99%
“…More research is needed to determine the most cost-effective method of seeding alfalfa and other legumes into improved tame pastures, including no-till methods such as frost seeding, feeding of the seed to cattle, or seed drilling with a notill drill. Indications of reductions in methane emissions from cattle on grass/legume pastures compared to cattle on pure grass stands (McCaughey et al 1997) or when finished in feedlots (Cohen et al 2004), and evidence of lower N 2 O emissions from legume stands than from N fertilized systems (Wagner-Riddle et al 1997), provide additional justification for such efforts.…”
Section: Livestock Productivity and Profitability Of Grazing Managemementioning
confidence: 99%